2012
DOI: 10.1371/journal.pone.0034929
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-Specific Accumulation of Amyloid β Induces Mitochondrial Dysfunction Leading to Apoptotic Cell Death

Abstract: Mitochondria are best known as the essential intracellular organelles that host the homeostasis required for cellular survival, but they also have relevance in diverse disease-related conditions, including Alzheimer's disease (AD). Amyloid β (Aβ) peptide is the key molecule in AD pathogenesis, and has been highlighted in the implication of mitochondrial abnormality during the disease progress. Neuronal exposure to Aβ impairs mitochondrial dynamics and function. Furthermore, mitochondrial Aβ accumulation has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
151
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(187 citation statements)
references
References 39 publications
6
151
0
Order By: Relevance
“…The Bcl-2 family of proteins, including Bax and Bim, was implicated in the execution machinery of oA␤-induced neuronal death (71)(72)(73) as well as the alteration of mitochondrial functions (52). The possible regulation of these mechanisms by Klotho requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The Bcl-2 family of proteins, including Bax and Bim, was implicated in the execution machinery of oA␤-induced neuronal death (71)(72)(73) as well as the alteration of mitochondrial functions (52). The possible regulation of these mechanisms by Klotho requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that Ab25-35 induced toxicity in cultured hippocampal neurons, which was consistent with previous studies (Arancibia et al 2008;Dong et al 2010;Resende et al 2007). We and other groups have further demonstrated Ab25-35 caused mitochondrial dysfunction in cultured neurons (Casley et al 2002;Cha et al 2012;Dong et al 2010). In the present study, we found a decrease in mtDNA copy number in cultured hippocampal neurons treated with Ab25-35.…”
Section: Discussionmentioning
confidence: 71%
“…Xie et al have observed severe structural and functional abnormalities of mitochondria in the immediate vicinity of Ab plaques (Xie et al 2013). Studies using neuronal cell culture demonstrated that Ab causes morphological alteration of mitochondria, ATP depletion, and production of ROS (Casley et al 2002;Cha et al 2012;Chen and Yan 2007;Dong et al 2010). The exposure of isolated mitochondria to Ab reduces complex IV activity (Canevari et al 1999) and induces the formation of the permeability transition pore (Du et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…33 The internalized receptor cargo is trafficked by localization signals within the ligand/receptor complex. 34 sCD44 internalization may involve mitochondrial dysfunction in a fashion similar to that of b-amyloid fragments, 35,36 causing abnormal mitochondrial function and cell death. The extent of exogenous b-amyloid co-localization in mitochondria is variable from partial without quantification [36][37][38] and 1% to 9%.…”
Section: Discussionmentioning
confidence: 99%
“…34 sCD44 internalization may involve mitochondrial dysfunction in a fashion similar to that of b-amyloid fragments, 35,36 causing abnormal mitochondrial function and cell death. The extent of exogenous b-amyloid co-localization in mitochondria is variable from partial without quantification [36][37][38] and 1% to 9%. 39 sCD44 is released by proteolytic cleavage 40 (shedding) from membrane-anchored CD44, which influences CD44-mediated HA binding to cell surfaces.…”
Section: Discussionmentioning
confidence: 99%